2019
DOI: 10.3390/membranes9020028
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Modification of Reverse Osmosis Membrane Elements for Enhanced Removal of Multiple Micropollutants

Abstract: Reverse osmosis (RO) membranes are widely used for desalination and water treatment. However, they insufficiently reject some small uncharged micropollutants, such as certain endocrine-disrupting, pharmaceutically active compounds and boric acid, increasingly present in water sources and wastewater. This study examines the feasibility of improving rejection of multiple micropollutants in commercial low-pressure RO membrane elements using concentration polarization- and surfactant-enhanced surface polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Further studies showed that MBR-RO achieved even better results with the removal of 20 compounds to below detection limits as compared to 13 compounds by MBR/NF [72]. A study conducted by Baransi-Karkaby et al reported the improved rejection of multiple EDCs and pharmaceutically active compounds (PhACs) by RO membrane elements using concentration polarization-and surfactant-enhanced surface polymerization [73]. The researchers performed experiments using RO membranes modified by grafting poly(glycidyl methacrylate) and as compared to commercial brackish water RO membranes.…”
Section: Agricultural Waste Emerging Contaminants Referencesmentioning
confidence: 99%
“…Further studies showed that MBR-RO achieved even better results with the removal of 20 compounds to below detection limits as compared to 13 compounds by MBR/NF [72]. A study conducted by Baransi-Karkaby et al reported the improved rejection of multiple EDCs and pharmaceutically active compounds (PhACs) by RO membrane elements using concentration polarization-and surfactant-enhanced surface polymerization [73]. The researchers performed experiments using RO membranes modified by grafting poly(glycidyl methacrylate) and as compared to commercial brackish water RO membranes.…”
Section: Agricultural Waste Emerging Contaminants Referencesmentioning
confidence: 99%
“…Re jection = 89.449 + 7.838A − 9.103D + 7.683AD − 0.680AE − 0.671ADE (4) For the permeate flux, except for factor B, all other main factors were significant, as well as the interactions AB, AD, AE, CD, CE, DE, ABD, ADE, and CDE, yielding the following relationship:…”
Section: Modeling For Predictions Of Permeate Flux and Antibiotic Rejmentioning
confidence: 99%
“…In fact, a great concern regarding antibiotics is that after administration, it is only partially absorbed by the patient, being the rest excreted in the urine or feces [2], reaching the urban sewage network and then the urban wastewater treatment plants (UWWTPs). In turn, these have conventional treatment processes, which are inefficient in removing antibiotics and other micropollutants [2][3][4]; thus, the discharged wastewater ends up contaminating the different ecosystems [5]. For this reason, UWWTPs are considered as one of the main sources of antibiotic release into the environment [6], discharging them in concentrations ranging from ng L −1 to µg L −1 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the membrane processes, reverse osmosis (RO) has been touted as an effective process to treat oily saline wastewater generated from oil and gas industry [ 8 , 9 ]. This technology is matured and capable in removing many types of molecules, including oil particles and ions, to yield fresh water that is suitable for potable and industrial uses [ 5 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%